Pengembangan Media Papan Flanel Menggunakan Metode Show and Tell untuk Meningkatkan Keterampilan Berbicara Anak Kelompok B di Paud Kemala Bhayangkari 06 Bima Kota Tahun Pelajaran 2020/2021 - Sri Kurniati; Fahruddin Fahruddin; Ika Rachmayani; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2021)
Speaking skill is the skill of producing speech sound to convey wishes, feelings, and desired to others. The purpose of this study was to find out the use of flannel board developed using the show and tell method to improve the speaking skills of group B children at PAUD Kemala Bhayangkari 06 Bima City in the academic year of 2020/2021 academic year. The study was developmental research with three stages. Each of which consisted of planning, implementation, observation, and analysis of the development. The subjects if this study were 8 children in group B. The methods of data collection used were observation and documentation. The data were analyzed using descriptive qualitative analysis. The results of the study on the use of flannel board developed using the show and tell method showed that the average children’s speaking skills increased, i.e 38,21% in development I, 72,35% in development II, and 95,42% in development III. In conclusion, the use of flannel board developed using the show and tell method could improve the speaking skills of group B children at PAUD Kemala Bhayangkari 06 Bima City.